Step
*
of Lemma
trivial-mFOL-rename
∀x,y:ℤ. ∀fmla:mFOL().  ((¬(y ∈ mFOL-freevars(fmla))) 
⇒ (fmla = mFOL-rename(fmla;y;x) ∈ mFOL()))
BY
{ RepeatFor 2 ((D 0 THENA Auto)) }
1
1. x : ℤ
2. y : ℤ
⊢ ∀fmla:mFOL(). ((¬(y ∈ mFOL-freevars(fmla))) 
⇒ (fmla = mFOL-rename(fmla;y;x) ∈ mFOL()))
Latex:
Latex:
\mforall{}x,y:\mBbbZ{}.  \mforall{}fmla:mFOL().    ((\mneg{}(y  \mmember{}  mFOL-freevars(fmla)))  {}\mRightarrow{}  (fmla  =  mFOL-rename(fmla;y;x)))
By
Latex:
RepeatFor  2  ((D  0  THENA  Auto))
Home
Index